TRIAGE AND MANAGEMENT OF MUSCULOSKELETAL INJURIES DURING EARTHQUAKE - Serkan Bayram; Gökhan Polat (İstanbul Tıp Fakültesi Dergisi)
The harm of earthquakes can be decreased with operative catastrophe planning and successful emergency assistance. First aid and triage organization are essential for the medical care of those trapped under the rubble after the earthquake. Every injury seen in orthopedics and traumatology practice can be observed with being under the rubble; these can be in a spectrum ranging from simple muscle crush to pelvis fracture with vascular injury. The main function of the orthopedist is to perform a quick diagnosis and accurate treatment to save the life and extremities. The first step in the management of limb and axial skeletal injuries is accurate immobilization of the injured region, such as a cervical collar for the cervical spinal segment. Maintaining a safe airway and large-bore intravenous access for hemodynamic stabilization are also priorities in traumatized patients. Surgical procedures related to orthopedics and traumatology can be classified as follows; emergency care, emergency surgeries, delayed surgeries, and planned surgeries. While performing all these surgical procedures, a multidisciplinary approach should be applied to monitor and treat the patient’s general condition.